Revolution and significance of “Green Energy Transition” in the context of new quality productive forces: A discussion on theoretical understanding of “Energy Triangle” - Caineng ZOU; Shixiang LI; Bo XIONG; Hanlin LIU; Feng MA (Petroleum Exploration and Development)
Considering the demands, situations and trends in respect to global climate change, carbon neutrality and energy transition, the achievements and significance of the global green energy transition and the new energy revolution of China are summarized, and the “Energy Triangle” theory is proposed. The research indicates that the energy technology revolution is driving a dual transformation in global energy: the black “shale oil and gas revolution” in North America and the green “new energy revolution” in China. The green energy revolution of China has achieved significant milestones in wind-solar-hydrogen-energy storage technologies, leading the world in photovoltaic and wind power. The country has developed the world’s largest, most comprehensive, and competitive new energy innovation, industrial and value chains, along with the largest clean power supply system globally. New quality productive forces represent the green productive forces. The green “new energy revolution” of China has accelerated the transformation of its energy structure and the global shift towards clean energy, promoting a new win-win model for the global green and low-carbon transition. Under the backdrop of a carbon-neutral goal-driven energy transition, the “Energy Triangle” theory within the framework of new quality productive forces explains the correlation and development of energy security, economic growth, and environmental sustainability throughout the evolution from fossil fuels to new energy systems, culminating in an energy revolution. Compared to the global energy resource endowment, the energy resources of China are characterized by abundant coal, limited oil and gas, and unlimited wind and photovoltaic energy. Moving forward, the energy strategies of China will focus on the advancement of technologies to clean coal for carbon emission reduction, increase gas output while stabilizing oil production, increase green energy while enhancing new energy, and achieve intelligent integration. Vigorously developing new energy is an essential step in maintaining the energy security of China, and establishing a carbon-neutral “super energy system” is a necessary choice. It is crucial to enhance the international competitiveness of China in new energy development, promote high-quality energy productive forces, support the country’s transition to an “energy power”, and strive for “energy independence”.